Nuclear acridine orange fluorescence in Rhizoctonia isolates from rice - Barrera, Viviana Andrea (2015)
The genus Rhizoctonia DC (1805) has long been studied as an important soilborne pathogen that causes a wide variety of symptoms because it is a non-specialized pathogen3. Rhizoctonia sensu lato is characterized by the lack of conidiogenous cells and this taxon is composed of two groups based on the number of nuclei per cell: the multinucleate group that belongs to Rhizoctonia s. str. and the binucleate group that belongs to Ceratorhiza5. Currently, other authors consider the group a Ceratobasidium–Rhizoctonia complex7 and divide it into two groups: BNR (binucleate Rhizoctonia-like) and MNR (multinucleate Rhizoctonia-like)9. Many methods are used to observe the number of nuclei in fungal cells, e.g. safranine O, aniline blue, HCl-Giemsa. Some of these methods apply a staining solution involving laborious, time-consuming procedures that require no equipment (Fig. 1). Other methods use fluorophores, which are rapid and precise